2016
DOI: 10.18632/oncotarget.10296
|View full text |Cite
|
Sign up to set email alerts
|

EFEMP1 promotes ovarian cancer cell growth, invasion and metastasis via activated the AKT pathway

Abstract: EFEMP1, a kind of extracellular matrix (ECM) protein, has been suggested to correlate with the development of different types of carcinoma. However, its functions in ovarian cancer remain unclear. In our study, we performed cDNA microarray analysis and identified EFEMP1 dramatically elevated in the highly invasive subclone, compared with the low invasive subclone. Lentivirus transfection experiments were constructed afterwards. The results demonstrated that knockdown of EFEMP1 significantly inhibited ovarian c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 30 publications
2
26
0
Order By: Relevance
“…Recent studies have yielded conflicting results about the function of fibulin-3 in tumor biology, showing that affinity or anti-tumor biological activity upon up- or downregulated expression depends on the type of cancer. In ovarian cancer 7 , 8 , osteosarcoma 9 , pancreatic cancer 10 , and glioblastoma 11 , fibulin-3 up-regulation was associated with poor prognosis because of malignant cell growth and invasion. On the other hand, downregulation of fibulin-3 in liver cancer 12 , 13 , gastric carcinoma 14 , lung carcinoma 15 , 16 , endometrial cancer 17 , and nasopharyngeal cancer 18 , was able to suppress cancer cell growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have yielded conflicting results about the function of fibulin-3 in tumor biology, showing that affinity or anti-tumor biological activity upon up- or downregulated expression depends on the type of cancer. In ovarian cancer 7 , 8 , osteosarcoma 9 , pancreatic cancer 10 , and glioblastoma 11 , fibulin-3 up-regulation was associated with poor prognosis because of malignant cell growth and invasion. On the other hand, downregulation of fibulin-3 in liver cancer 12 , 13 , gastric carcinoma 14 , lung carcinoma 15 , 16 , endometrial cancer 17 , and nasopharyngeal cancer 18 , was able to suppress cancer cell growth and metastasis.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, carbonic anhydrase 9 (CA9) and angiopoietin‐related protein 4 (ANGPTL4), proteins known to respond to tumor hypoxia (Sedlakova et al , ; Carbone et al , ), showed 13‐ and 3.6‐fold increases, respectively, in tumor tissue (Fig D and Appendix Table S1). Finally, EGF‐containing fibulin‐like extracellular matrix protein 1 (EFEMP1), which binds to epidermal growth factor receptor (EGFR) to promote tumor growth, invasion, and metastasis (Yin et al , ), showed a threefold increase across seven O‐linked glycosylation sites in tumor tissue (Fig D and Appendix Table S1). By contrast, both IGHA1 and MUC1, known O‐linked glycoproteins, showed no detectable change between normal and tumor tissue indicating that the changes in O‐linked glycoproteins observed in tumor tissue are highly selective.…”
Section: Resultsmentioning
confidence: 99%
“…Through previous studies, we found that EFEMP1 was involved in the regulation of many biological processes in carcinoma, suggesting that EFEMP1 may play an important role in the development of HCC. When the transcription of EFEMP1 was inhibited, how did it cause phenotypic changes in HCC cells, and by what kind of signaling pathway to affect HCC?…”
Section: Resultsmentioning
confidence: 96%